Continuous treatment of the organic fraction of municipal solid waste in an anaerobic two-stage membrane process with liquid recycle - Trzcinski, A.P. (2017)
The stability and performance of a two-stage anaerobic membrane process was investigated at different organic loading rates (OLRs) and Hydraulic Retention Times (HRTs) over 200 days. The Hydrolytic Reactor (HR) was fed with the Organic Fraction of Municipal Solid Waste (OFMSW), while the leachate from the HR was fed continuously to two Submerged Anaerobic Membrane Bioreactors (SAMBR1 and 2). The Total COD (TCOD) of the leachate varied over a wide range, typically between 4000 and 26,000 mg/L while the Soluble COD (SCOD) in the permeate was in the range 400–600 mg/L, achieving a COD removal greater than 90% at a HRT of 1.6–2.3 days in SAMBR1. The operation was not sustainable below this HRT due to a membrane flux limitation at 0.5–0.8 L/m2 h (LMH), which was linked to the increasing MLTSS. SCOD in the recycled permeate did not build up indicating a slow degradation of recalcitrants over time. SAMBR2 was run in parallel with SAMBR1 but its permeate was treated aerobically in an Aerobic Membrane Bioreactor (AMBR). The AMBR acted as a COD-polishing and ammonia removal step. About 26% of the recalcitrant SCOD from SAMBR2 could be aerobically degraded in the AMBR. In addition, 97.7 % of the ammonia–nitrogen was converted to nitrate in the AMBR at a maximum nitrogen-loading rate of 0.18 kg NH4+–N/m3 day. GC–MS analysis was performed on the reactor effluents to determine their composition and what compounds were recalcitrant.